Marsdenia tenacissima (Roxb.) Moon injection exerts a potential anti-tumor effect in prostate cancer through inhibiting ErbB2-GSK3β-HIF1α signaling axis. (15th September 2022) - Chen, Xin; Luo, Zhuo; Liu, Xi; Li, Xiaolan; Li, Qiaofeng; Zhang, Weiquan; Liu, Ying; Cheng, Zhiping; Yang, Xin; Liu, Yanying; Jin, Ronghua; Zhu, Dan; et al.
Abstract: Ethnopharmacological relevance: Marsdenia tenacissima injection (MTE), a traditional Chinese medical injection extracted from the rattan of Marsdenia tenacissima (Roxb.) Moon, has been approved for clinical use in China as an adjuvant therapeutic agent in multiple cancers, including esophageal cancer, gastric cancer, lung cancer, and liver cancer. However, the activity and mechanism of MTE on prostate cancer (PCa) remain to be defined. Aim of the study: To investigate the activity and the underlying mechanism of MTE in the treatment of PCa. Materials and methods: The component characterization of MTE was analyzed by HPLC-CAD-QTOF-MS/MS technology. Cell Counting Kit-8 (CCK-8) assay was used to assess PCa cell proliferation. Colony formation assay was applied to detect the clonogenic ability of the cells. MetaboAnalyst5.0 database was employed to analyze the altered metabolites of PC3 cells treated with MTE obtained by UPLC-QTOF-MS/MS. Combined with metabolomics analysis and network pharmacology, we predicted the potential targets, which further were verified by Western Blot, RT-qPCR, and Immunohistochemistry assays. Finally, SeeSAR software was applied to predict the potential active components of MTE against PCa. Results: A total of 21 components in MTE were confirmed by HPLC-CAD-QTOF-MS/MS analysis. MTE inhibited the proliferation and colony formation of PCa cells. A total of 20 metabolites closely related to glycerophospholipid metabolism, glycolysis/gluconeogenesis, and tricarboxylic acid (TCA) cycle were significantly changed in PC3 cells treated with MTE. The network pharmacology analysis revealed that MTE suppressed the growth of PC3 cells might by regulating the ErbB2-GSK3β-HIF1α signaling axis. Furthermore, we also confirmed that stimulation of MTE significantly inhibited the phosphorylation of ErbB2 at Tyr877 and the activities of its downstream signal transducers (GSK3β and HIF1α) in PCa, as well as the mRNA levels of critical factors (IDH2, LDHA, and HIF1A) in the tricarboxylic acid (TCA) cycle. Molecular docking further suggested that Tenacissimoside E, cryptochlorogenic acid, and scopoletin might be the active ingredients of MTE for PCa treatment. Conclusion: This study proposed that MTE exerts a potential anti-tumor effect in PCa through inhibiting ErbB2-GSK3β-HIF1α signaling axis, which may be related to the TCA cycle. Graphical abstract: Image 1 Highlights: MTE inhibits the proliferation of PCa cells. ErbB2-GSK3β-HIF1α signaling axis is involved in the activity of MTE against PCa. MTE alters the metabolism of PC3 cells by reducing the mRNA levels of IDH2 and LDHA.